Wandance. 1 - Coffee (Manga author) (Kodansha USA Publishing Ltd., 2022)
"Kaboku Kotani is starting high school, and he plans to do what he's always done: go along with his friends, keep quiet, and not draw too much attention to himself. After all, it's hard enough to get by with a stutter like his-- why make things worse by standing out from the crowd? But then he sees another first-year, Hikari Wanda, dancing like no one is watching-- or like she doesn't care who sees her. It makes Kaboku wonder: Could he reach that same freedom? To find his way to Wanda, he does something he never thought he could: He joins the dance club. After all, every routine begins with a single step, right?" -- Back cover.